Cigarettes Smoking Pattern in Patient with Urothelial Carcinoma of the Bladder after Smoking Cessation in Tertiary Hospital - Novesar, Aidil Rahman; Pramod, Sawkar Vijay; Safriadi, Ferry (Asian Pacific Journal of Cancer Care, 2022)
Background: Urothelial carcinoma is the most widely recognized histologic type of bladder cancer. Smoking duration and intensity associated with tumour aggressiveness and recurrence. This study aims to examine smoking behavioural change in patients with bladder urothelial carcinoma who were given an intervention for smoking cessation. Methods: A cross-sectional study (2009 – 2019) was conducted. Subjects were divided into three groups: patients who had smoked <20 cigarettes per day for ≤30 years; patients who had smoked for 31–40 years or had smoked >20 cigarettes per day for ≤30 years; and patients who had smoked for >40 years. General characteristics, educational level and quit levels are noted. These data were obtained from the medical record and anamnesis by telephone. Result: A total of 325 patients with urothelial cancer between 2009-2019 were involved. 273 (84%) patients were male, aged 58.71 ± 12.8 years. 40.9% had a history of smoking for >40 years, 66.5% of patients did not quit smoking at all. There was a significant difference in smoking cessation rates between groups with a history of different smoking intensities (p = 0.000). Mann-Whitney U test showed that there was a significant difference between the group who had a history of smoking <20 cigarettes for ≤30 years and the group who smoked for 31-40 years or >20 cigarettes per day for ≤30 years with the group who smoked for >40 years (p = 0.000 on both comparisons). 135 (41.5%) patients were in the lower education group. Conclusion: The patient’s history of heavy smoking intensity and lower educational level was associated with a lower likelihood of smoking cessation. Urologists must play an important role in the education and intervention process to support patients to quit smoking. A guide/guideline is needed and it could be through a special smoking clinic for counselling or treatment.